Mediation as an alternative method of conflict resolution in the opinion of secondary school students - Marianna Karolina Klimek (Rozprawy Społeczne)
Abstract Mediation is considered to be an effective method of conflict resolution. For this reason, it's more and more often transferred to the educational field. The aim of the article is to check the awareness of young people from secondary schools in Biała Podlaska, regarding mediation as a method of conflict resolution at school.